Keunggulan Komparatif dan Kompetitif dalam Produksi Padi di Kabupaten Lampung Tengah Propinsi Lampung - Zulkarnain, Zulkarnain; Haryono, Dwi; Kasymir, Eka (Jurnal Penelitian Pertanian Terapan, 2010)
This objective of tis research was to: 1) Determine whether the Central Lampung District has a comparative advantage and competitive advantage in rice production. 2) Determine how the sensitivity of changes in output prices and input prices to the comparative and competitive advantage in rice production. Location of the study was conducted at the Rama Utama Village and Ramayana Village, Seputih Raman Subdistrict of Central Lampung District. This research was conducted by survey and interview methods to farmers by using a questionnaire that had been prepared. Respondents in this research is rice farmer in the Seputih Raman subdistrict of Central Lampung District, totally 73 farmers were selected by simple random sampling method (simple random sampling). Types of data used are primary and secondary data obtained through direct interviews and offices or agencies. To answer the first objective analysis was used Policy Analysis Matrix (PAM) and to answer the second objective was used sensitivity analysis. Results showed that: 1) rice farming in Central Lampung District has a comparative advantage and competitive advantage with a value of PCR (Private Cost Ratio) equal to 0.4635 and the value of the DRC (Domestic Resource Cost) of 0.4368 so that feasible and profitable to be conducted. 2) comparative and competitive advantage of rice production in Central Lampung District is sensitive to changes in output prices. Increase or decrease of output prices will affect the comparative and competitive advantage of of rice production in Central Lampung District. Keywords: Comparative Advantage, Competitive, Paddy Production